Kairos a fotografia - Kłosek, Sebastian (Collectanea Philologica, 2015)
Problem of time was widely discussed in Greek antiquity. Numerous definitions of time indicatethat the phenomenon was not clear to the ancient people. Kairos was among of them. It describedthe unique moment, which was bringing to a halt normal course of time and allowed a changeto happen. And nowadays, Kairos is still considered as faint moment that if not captured, disappearsirretrievably. This paper analyzes the connection between Kairos and the contemporary art medium– photography, which main idea is to catch and hold the very special moments.